Contribution of coffee agroforestry to the income of farmers in Tulungrejo Village, Ngantang District, Malang Regency - Joko Triwanto; Fatan Ghani Rizaldy Arrofi; Erni Mukti Rahayu (Jurnal Penelitian Kehutanan Wallacea, 2022)
The potential for coffee development in Indonesia has great opportunities, supported by high market demand. The purpose of the study was to determine the characteristics of coffee agroforestry and its contribution to the income of farmers in Tulungrejo Village, Ngantang District, Malang Regency. Types of data consist of primary data and secondary data. Primary data were obtained from interviews with 90 respondents of coffee agroforestry farmers who are members of the Forest Farmers Village Partnership Institute (LKDPH). Data processing used quantitative descriptive analysis by calculating production costs, revenues, and income, as well as the contribution of coffee agroforestry to the total income of farmers. The results showed that farmers applied agrisilviculture with a simple system, namely planting robusta coffee (Coffea canephora) under forest tree stands. The value of the R/C ratio is 2.98 where the value is >1, meaning that coffee agroforestry farming provides benefits. The application of coffee agroforestry contributes significantly to the total income of farmers, which is 58.47%. The development of coffee agroforestry is directed at increasing productivity and quality without damaging the shade plants. The policy implications of coffee agroforestry development must involve all relevant parties including the government, entrepreneurs, farmer groups, banks, and cooperatives.